Management of Acute Lower Limb Ischemia at Osh Regional Clinical Hospital, Kyrgyzstan: A Retrospective Analysis of Amputation Patterns and Case Report - Adilbek, Zhanbaev; Anara Kenesovna, Zhanbaeva; Bukarbaevna, Imetova Jazgul; Aijan Tashpolotova, Matkasymova (Journal of Neonatal Surgery, 2025)
Background: Acute lower limb ischemia (ALLI) is a major vascular emergency that frequently requires amputation and is associated with high morbidity and mortality worldwide. In low- and middle-income countries such as Kyrgyzstan, the absence of advanced diagnostics, delayed interventions, and high incidence of comorbidities, including diabetes and atherosclerosis, worsen the prognosis. The purpose of this study is to determine the etiological patterns, amputation levels and clinical outcomes of 52 patients with ALLI in Kyrgyzstan from 2020 to 2021. The importance of this study is to respond to a significant public health issue in the region, where constraints in resources and the increasing incidence of diabetes and post-COVID complications increase the burden of limb ischemia. Methods: A retrospective analysis was made on 52 patients who underwent lower limb amputations for ALLI at a tertiary care centre in Kyrgyzstan from 2020 to 2021. The data on demographics, etiology, amputation levels, rates of reamputation and clinical indications were analyzed. Results: The majority of cases (60%) were secondary to obliterative atherosclerosis of the lower limb vessels, followed by diabetes-related vascular complications in 28.8%, and 11.4% post COVID-19 pneumonia associated thrombosis. Above knee amputations were the most common procedure (32 patients), however diabetic foot syndrome cases needed different management approaches, i.e., 5 thigh, 5 lower leg, 2 foot, and 3 toe amputations. Four patients (7.7%) needed re-amputation, and wet gangrene was the main reason for surgery in 59.6% of cases. Conclusion: In Kyrgyzstan, this study shows that atherosclerosis and diabetes are the predominant causes of ALLI. The emerging thrombotic risks found in this study are all linked to COVID-19, which further complicates the management of limb ischemia in the setting of a resource-limited country like Kyrgyzstan, where delayed presentations and limited access to revascularization techniques are associated with high amputation rates. These challenges highlight the urgent need for improved vascular care infrastructure, early diagnosis, and multidisciplinary management in resource-limited settings like Kyrgyzstan where, because of delayed presentations and limited access to revascularization techniques, high amputation rates are seen. These challenges are exemplified by the clinical case discussed in the article, for which preventive strategies and tailored healthcare policies are crucial to decrease the socioeconomic and medical burden of limb ischemia.